Soil Quality Changes in Open-Pit Nickel Mining and Post-Mining Reclamation: Implications for Achieving SDG 15 (Life on Land) - Muchammad Asyroful Fawaid; Kurniawan Sigit Wicaksono; Reni Ustiatik (Postgraduate, University of Mataram, 2026)
Open-pit nickel (Ni) mining has expanded rapidly in Indonesia and has become one of the main drivers of land degradation. This review synthesizes scientific evidence on the impacts of open-pit Ni mining on soil properties and evaluates the application of the Soil Quality Index (SQI) as integrative tools for assessing soil degradation and reclamation success. The reviewed studies consistently report severe declines in soil quality following mining, including reductions in soil organic carbon (SOC) from approximately 40.2 g/kg in forest soils to as low as 2.29 g/kg in post-mining soils, increases in bulk density from around 0.88 g/cm to 1.37 g/cm, and substantial decreases in microbial biomass carbon 350 mg C/kg to below 110 mg C/kg in heavily disturbed areas. Sensitive indicators such as soil organic matter, pH, bulk density, microbial biomass carbon, soil respiration, and enzyme activities were identified as key variables responding rapidly to mining disturbance and reclamation measures. Reported SQI values range from very low in active mining areas (0.18–0.30), moderate in reclaimed lands (0.43–0.55), and high in forest ecosystems (0.70–0.81). These findings demonstrate that SQI provides a science-based framework for monitoring post-mining restoration and supports the achievement of SDG 15 (Life on Land), particularly land degradation neutrality targets.